A biodegradable bismuth–gadolinium-based nano contrast agent for accurate identification and imaging of renal insufficiency in vivo. Issue 21 (15th September 2021) - Zhang, Jing; Song, Kang; Ping, Jing; Du, Jun; Sun, Yun; Zhang, Jianping; Qi, Ming; Miao, Yuqing; Li, Yuhao
Abstract : A biodegradable gadolinium-doped mesoporous bismuth-based nanomaterial is used to diagnose kidneys with dysfunction accurately via magnetic resonance imaging in vivo . Abstract : Magnetic resonance imaging (MRI) with excellent contrast for soft tissue imaging is often used for the diagnosis of kidney disorders, but its resolution is not high and requires the assistance of contrast agents. Because the retention time of small molecules in the kidneys is too short and they are metabolized quickly, it is necessary to design a nano-sized material for enhancing the imaging of the kidneys, thereby increasing its residence time and monitoring the lesion site in real time. For that, we designed and synthesized a new kind of nano dual-modal contrast agent (BiGd–PVP) with MR/CT imaging function for accurate identification and imaging of renal insufficiency in vivo . BiGd–PVP can interact with glutathione in the kidneys and slowly release water-soluble Gd 3+ ions to enhance the MRI contrast ability. Due to their size advantage, BiGd–PVP nanomaterial can accumulate and stay in the kidneys for a longer time, and because of the degradation properties, they can also be gradually excreted from the kidneys. The metabolism of BiGd–PVP in an impaired kidney will be slower than that in a healthy kidney. Thus, taking advantage of this feature, through BiGd–PVP-mediated MR imaging, it is easy to distinguish between healthy kidneys and impaired kidneys.